Stability enhancement of aldehyde dehydrogenase from Anoxybacillus geothermalis strain D9 immobilized onto Seplite LX120 - Latip, Wahhida; Rosli, Nur Ezzati; Mohamad Ali, Mohd Shukuri; Ahmad Kamarudin, Nor Hafizah; Raja Abd Rahman, Raja Noor Zaliha (MDPI AG, 2023)
Enzyme stability is regarded as an important criterion for an industrial biocatalyst. Aldehyde dehydrogenase (ALDH) from A. geothermalis strain D9 was previously reported to exhibit good thermostability. However, this enzyme is still not suited to use in harsh environments. In this current work, we aim to see the viability of ALDH in terms of stability when immobilized into Seplite LX120. The purified ALDH was successfully immobilized via physical ad-sorption at 4 h with 1.25 mg/mL enzyme loading. The immobilized ALDH exhibited improved stability compared to free ALDH as the optimum temperature increased up to 80 °C and was stable with temperatures ranging from 30 to 90 °C. It was also stable in broad pH, ranging from pH 4 to pH 12. Moreover, more than 50 of the immobilized ALDH activity was retained after being stored at 25 °C and 4 °C for 9 and 11 weeks, respectively. The reusability of immobilized ALDH is up to seven cycles. The corroboration of ALDH immobilized on the Seplite LX120 was verified via Fourier-transform infrared spectroscopy, scanning electron microscopy, and a re-duction in the surface area. The improved features of immobilized ALDH, especially in enzyme stability, are important for future applications.